Functional properties of spray-dried whole blood powder - Magat, Rowena Pangilinan; Sales, Alicia C. (1981.)
ABSTRACT Pig's blood was spray-dried into powder at 180°F. The spray-dried whole blood powder was evaluated in terms of functional properties, proximate analysis and microbiological quality. The functional tests revealed that spray-dried whole blood powder is most soluble at pH 3. A solution with 8% protein concentration, whipped for 6 minutes has a good foaming capacity and stability at pH 9. At 10% concentration, a solution of spray-dried whole blood powder formed a gel; however, higher concentrations are needed to obtain a more rigid and firm gel. The powder exhibited an excellent wetting capacity. Results of proximate analysis and microbiological quality indicated that the spray-dried whole blood powder is an excellent source of protein and it is microbiologically safe as indicated by the absence of pathogens.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Blood -- Analysis; Blood for food and medicine